Expert Validation of Learning Videos About Plant Tissue for Class XI - alifa, laily; Ami, Mucharommah Sartika; Meishanti, Ospa Pea Yuanita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The modern era today is characterized by a revolutionary technological transformation, which fundamentally changes the paradigm of human life, including in the context of education and the teaching process. The integration of technology in the context of education can be done through the use of technological resources as innovative learning media, one of which is audio-visual media. The purpose of this study is to describe the feasibility of audio-visual media developed based on the assessment of material experts and learning media experts. The type of research used in this study is Research and Development. The method used is development research which refers to the ADDIE model. The analysis stage is carried out in the form of analyzing the needs for the development of audio-visual media. The design stage is in the form of designing a developed media storyboard. The development stage is in the form of media development followed by validation activities of material experts and learning media experts. The results of the study show that the feasibility of the developed audio-visual media is assessed through expert assessment, which includes material experts and media experts. The feasibility results of the plant tissue material obtained the results of a feasibility test by material experts of 85.71% with the criterion of